Media Pembelajaran Interaktif Untuk Mata Pelajaran Matematika - Toha, Agung Fuad Moch; Khasanah, Fata Nidaul (Jurnal Kajian Ilmiah, 2020)
Abstract A learning model that is widely applied to schools is a model of lecture learning with one-way communication, where the action is the teacher, while the student only enables the sense of vision and the sense of hearing. Conventional learning models are considered to be less exploring students ' knowledge, attitudes, and student behavior. One solution to help conventional learning is to use more practical interactive learning media. The development Model in this study uses the Multimedia Development Life Cycle (MDLC). Multimedia Development Life Cycle (MDLC) with the stages of development model is concept (concept), design (design), obtaining content material (collection of materials), assembly (preparation and manufacture), and testing (trials). The results of the study showed interactive media applications in assisting students to understand the subjects of mathematics running in accordance with its functionality. Keywords: Interactive Media, Media Learning, Multimedia Development Life Cycle Abstrak Model pembelajaran yang banyak diterapkan pada sekolah adalah model pembelajaran ceramah dengan komunikasi satu arah, dimana yang aktif adalah guru, sedangkan siswa hanya memfungsikan indera pengelihatan dan indera pendengarannya. Model pembelajaran konvensional dianggap kurang mengeksplorasi wawasan pengetahuan siswa, sikap dan prilaku siswa. Salah satu solusi untuk membantu pembelajaran konvensional tersebut adalah dengan memakai media pembelajaran interaktif yang lebih praktis. Model pengembangan dalam penelitian ini menggunakan Multimedia Development Life Cycle (MDLC). Multimedia Development Life Cycle (MDLC) dengan tahapan model pengembangan yaitu concept (konsep), design (desain), obtaining content material (pengumpulan bahan), assembly (penyusunan dan pembuatan) dan testing (uji coba). Hasil dari penelitian menunjukkan aplikasi media pembelajaran interakstif dalam membantu siswa untuk memahami mata pelajaran Matematika berjalan sesuai dengan fungsionalitasnya. Kata kunci: Interaktif Media, Media Pembelajaran, Multimedia Development Life Cycle